Comparative Study of Cutaneous Wound Repair Observed in Probiotic in Relative To Antibiotic Therapy in Rat Model - Hina Khan, Muhammad Rafique, Syed Nyder Raze Naqvi, Afroz S. Qazi , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2014)
Objective: To observed the substantial evidence regarding the significance of probiotics in cutaneous wound repair in comparison with antibiotic treated group in rat model. Place & Duration; Experimental study, conducted in the department of Anatomy. Al-Tibri Medical College Isra University Karachi Campus. From June 2013 to October 2013. Material & Methods: Sixty Albino rats were taken and divided in to three groups on the bases of topical applications, Group A control (normal saline), Group B (Probiotics) and Group C (Antibiotic ). Each group is further divided into sub group on the bases of day of sampling, A 1 ( day 03 ), A2 (day 07), A3 (day14) and A4 (day 21). Sample was taken on day 3. 7 ,14 and 21 from each group and tissues were processing and stained to observed the neutrophil count, that shows the rapid phase of healing process. Data were analyzed on SPSS version 17 by applying ANOVA post hoc Tuckey's test. Results: The mean ± SD of the neutrophil count of Group A (Control) and Group C (Antibiotic) compared with the neutrophil count of Group B ( Probiotics) ix400. Results shows comparison between Group B and A were Mean + SD of numbers of Neutrophils 1 x400 in groups B 1 were 7.2700 ± 6.26085, B2 5.2950 ± 6.02407, B3 2.7725 ± 3.37920, B4 2.5000 ± 1.29099 and in Al were 23.2500 ± 2.21736, A2 29.7500 ± 4.64579, A3 25.0000 ± 7.11805 and A4 15.0000 ± 3.55903. The significant value was in B1 and Al (P = 0.000), B2 and A2 (P=0.000), B3 and A3 (P=0.000) and B4 and A4 (P=0.000), The result Showed decreased number of Neutrophils in Group B in comparison with A. Results of comparison between Group B and Group C were Mean ± SD of numbers of Neutrophils i x400 in groups B1 were 7,2700 ± 6.26085, B2 5.2950 ± 6.02407, B3 2.7725 ± 3.37920. B4 2.5000 ± 1.29099 and Cl 22.0000 + 8.12404, C2 20.0000 ± 2.44949. C3 18.0000 ± .81650 and C4 10.7500 ± 2.21736. While comparing the group Bl and C 1 p value was (P=0,001), B2 and C2 (P=0.001), B3 and C3 (1)=0.001) and B4 and C4 (P-0.001 ). Conclusion: Probiotics shows strong anti-inflammatory status in comparison with other therapeutic groups.